Randomised clinical trial: effects of monotherapy with ADX10059, a mGluR5 inhibitor, on symptoms and reflux events in patients with gastro‐oesophageal reflux disease - Zerbib, F.; Bruley des Varannes, S.; Roman, S.; Tutuian, R.; Galmiche, J.‐P.; Mion, F.; Tack, J.; Malfertheiner, P.; Keywood, C. (Alimentary pharmacology & therapeutics, 2011)
Aliment Pharmacol Ther 2011; 33: 911–921 Summary Background  ADX10059, a metabotropic glutamate receptor 5 (mGluR5) negative allosteric modulator, has been shown to reduce gastro‐oesophageal reflux events and oesophageal acid exposure in patients with gastro‐oesophageal reflux disease (GERD) and healthy subjects. Aim  To evaluate the effects of ADX10059 monotherapy for 2 weeks on symptom control in patients with GERD. Methods  This was a double‐blind, placebo‐controlled, multi‐centre trial in GERD patients who were responders to proton pump inhibitors (PPIs). Following PPIs withdrawal, a 2‐week baseline washout period was followed by 2‐week treatment with either ADX10059 120 mg or placebo b.d. The primary clinical efficacy endpoint was the number of GERD symptom‐free days in treatment week 2 compared with the last 7 days of baseline. The effect on reflux events using 24‐h impedance–pH monitoring was also determined in a subset of 24 patients. Results  The full analysis set comprised 103 patients ADX10059 (N = 50), Placebo (N = 53). In treatment week 2, ADX10059 significantly increased GERD symptom‐free days (P = 0.045) and heartburn‐free days (P = 0.037), reduced antacid use (P = 0.017), improved total symptom score (P = 0.048) including subscale heartburn/regurgitation (P = 0.007) and sleep disturbance because of GERD (P = 0.022). ADX10059 significantly reduced total (P = 0.034) and acidic reflux events (P = 0.003). ADX10059 was well tolerated. Most common adverse events for ADX10059 were mild to moderate dizziness 16% and vertigo 12% (placebo 4% and 2%). Conclusions  Inhibition of mGluR5 with ADX10059 monotherapy reduces reflux events and improves symptoms in GERD patients. This mechanism has promise for the management of GERD (ClinicalTrials.gov, number NCT00820079).